Sikap Perlindungan Diri Terhadap Pelecehan Seksual Pada Siswa Sekolah Menengah Pertama Banda Aceh - Ambiya, Fajarrul; Bustamam, Nurbaity; Bakar, Abu (Jurnal Suloh, 2023)
Sexual harassment is a form of sexual coercion in which a person makes another person the target of unwanted comments, solicitations, gestures, physical contact, or direct requests from the other party, in order to obtain a sexual advantage. Sexual harassment can occur in many settings, including the workplace, school, or consulting a therapist. The purpose of this study was to describe the knowledge of Banda Aceh junior high school students about self-protection from sexual harassment and also to obtain an overview of the availability of knowledge sources regarding self-protection from sexual harassment in junior high school adolescents in Banda Aceh. This study uses a survey method with a descriptive quantitative approach. The results showed that the percentage calculation obtained an average high category from these results, which was 84%. This shows that public junior high school students in Banda Aceh already know about self-protection from sexual harassment, although there are still 16% of public junior high school students in Banda Aceh who do not know about self-protection from sexual harassment. The calculation of the average percentage of the high category regarding the availability of sources from parents as a result of research is 85%. This shows that parents of junior high school students in Banda Aceh have provided knowledge to their children about self-protection from sexual harassment, as well as the calculation of the average percentage of the medium category regarding the availability of resources from teachers, the results of the study are 62%. This shows that junior high school teachers in Banda Aceh have provided knowledge to their students about self-protection from sexual harassment, while sources from friends indicate a low average percentage calculation from the results of the study, which is 27%. This shows that it is relatively low for junior high school students in Banda Aceh to have friends who have discussed knowledge about self-protection from sexual harassment